(untitled) (Eduscotech, 2024)
This study aims to analyze the fulfillment of the right to education for children with special needs (ABK) within the framework of educational legal politics in Magetan Regency. Education is a constitutional right of every citizen without discrimination, including children with special needs; however, various structural, cultural, and juridical constraints continue to affect the implementation of inclusive education policies. This research employed a qualitative approach using a case study method, with data collected through interviews, observations, and documentation. The findings indicate that, normatively, policies concerning education for children with special needs are supported by strong legal foundations at both national and local levels. Nevertheless, their implementation has not been fully optimized due to limited human resources, inadequate facilities, and insufficient understanding of inclusive education principles among key stakeholders. This study is expected to contribute to policy evaluation and to inform improvements in the implementation of inclusive education.